Metformin Use on Incidence and Oncologic Outcomes of Bladder Cancer Patients With T2DM: An Updated Meta-Analysis - Liu, Chen-Qian; Sun, Jian-Xuan; Xu, Jin-Zhou; Qian, Xiao-Yuan; Hong, Sen-Yuan; Xu, Meng-Yao; An, Ye; Xia, Qi-Dong; Hu, Jia; Wang, Shao-Gang (Frontiers in Pharmacology, 2022)
Background: The incidence rate and mortality of bladder cancer are increasing year by year. Interestingly, the commonly used metabolic regulatory drug metformin has been reported to have anti-tumor effect in recent years. Nevertheless, it keeps unclear whether the usage of metformin is beneficial or unbeneficial in treating bladder cancer. Thus, a meta-analysis was conducted to explore the long-term effect of metformin on the incidence of bladder cancer and OS, PFS, DSS and RFS in patients with bladder cancer. Method: We aim to collect evidence of the association between the usage of metformin and the incidence and treatment outcome of bladder cancer. We searched PubMed, Embase, Ovid Medline and Cochrane Library up to February, 2021 to get effective literature reporting the effects of metformin in bladder cancer. The main outcomes were the protective effects of metformin on the incidence, overall survival (OS), recurrence-free survival (RFS), progression-free survival (PFS), and disease-specific survival (DSS) of bladder cancer. And OR (odds ratio) and HR (hazard ratio) with their 95%CI were pooled. Two independent researchers assessed the quality of included studies using the Newcastle-Ottawa Scale (NOS). Results: We involved 12 studies meeting the inclusion criteria, including a total of 1552773 patients. The meta-analysis showed that use of metformin could decrease the incidence (OR=0.45, 95%CI=0.37-0.56; P<0.01) and prolong recurrence-free-survival (HR=0.56, 95%CI=0.41-0.76; P=0.91) of bladder cancer. However, there were no significant protective effects in the overall survival (HR=0.93, 95%CI=0.67-1.28, P=0.05), disease-specific-survival (HR=0.73, 95%CI=0.47-1.16; P=0.01), and progression-free-survival (HR=0.78, 95%CI=0.53-1.15, P=0.34). Conclusion: The results revealed that the usage of metformin could reduce the incidence of bladder cancer and prolong the prognosis of bladder cancer, respectively. More prospective studies are needed to prove the protective role of metformin on bladder cancer.